What do we study studying body? Researcher’s attempts to embodiment research - Byczkowska, Dominika (Qualitative Sociology Review, 2009)
The article presents researcher’s attempts, methodological problems and queries in embodiment research during a Grounded Theory Methodology based study on social world of ballroom dancers. The research has been conducted among ballroom dancers, flamenco dancers, belly dancers, dance instructors, choreographers and judges. One of the aspects of the research is social construction of embodiment. In the article I will present techniques and methods of research such as autoetnography, interview, observation, photo and video analysis as well as kind of results they may give and what is really studied when using these methods. I will also present how one experiences his/her body in this group. I will try to answer a question: what is the real result of researcher’s attempts in embodiment study in sociology; do we really study body, or its social practices, socially constructed individual experience; how deeply can we make the research when our object (somebody else’s body) is not entirely intersubjectively available for our recognition.